2018
DOI: 10.1016/j.celrep.2018.06.056
|View full text |Cite
|
Sign up to set email alerts
|

COMMD5/HCaRG Hooks Endosomes on Cytoskeleton and Coordinates EGFR Trafficking

Abstract: COMMD5/HCaRG is involved in tissue repair, and its low expression is associated with tumorigenicity. Cell growth, migration, and differentiation are controlled by COMMD5. We previously reported that COMMD5 inhibited the growth of renal carcinoma cells by regulating expression or phosphorylation of ErbB members. Here, we demonstrate that COMMD5 is crucial for the stability of the cytoskeleton. Its silencing leads to a major re-organization of actin and microtubule networks. The N terminus of COMMD5 binds to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…This result is in agreement with the previously published proteomics data showing that WASH levels are increased in hepatocytes from Commd1 and Commd6 tissue-specific knockout mice that show defective LDLR recycling 32 . Furthermore, they are in agreement with a recent study that identified a number of alterations in cytoskeletal structure in COMMD5-deficient cells 61 . Altogether these data suggest that the enhanced endosomal accumulation of WASH in CCC-deficient states is physiologically detrimental.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with the previously published proteomics data showing that WASH levels are increased in hepatocytes from Commd1 and Commd6 tissue-specific knockout mice that show defective LDLR recycling 32 . Furthermore, they are in agreement with a recent study that identified a number of alterations in cytoskeletal structure in COMMD5-deficient cells 61 . Altogether these data suggest that the enhanced endosomal accumulation of WASH in CCC-deficient states is physiologically detrimental.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together this data supports the notion that an important role of Commander is to facilitate trafficking between endosomes and the Golgi. Further evidence for a role in endosomal trafficking is the interaction of Commd5 with the small GTPase Rab5 . Commd5 depletion disrupts both the F‐actin and microtubule cytoskeletons and results in Rab5‐positive endosomes more peripherally localised in the cell.…”
Section: Retriever CCC and The Commander Complexmentioning
confidence: 99%
“…Among the various COMMD proteins the sequence of this HN domain is highly variable, indeed only through secondary structure predictions was it possible to show the domain is structurally similar in all family members. To date the only potential ligands for the HN domain that have been identified are Rab5 and tubulin binding to Commd5 and Commd1 . Its high degree of sequence variability suggests it may impart either specific functions to the different homologues, or that it may help define the precise architecture and stoichiometry of larger COMMD oligomers.…”
Section: Structures Of the Commd Proteinsmentioning
confidence: 99%
“…40 Over the last decades, increasing evidence has uncovered the underlying mechanisms involved in tumorigenesis and progression of pRCC, and it was gradually acknowledged that alternation in MET pathway was the main cause of type 1, whereas type 2 was more related to activation of the F I G U R E 8 Construction of SF-AS correlation network in pRCC. Moreover, KEGG analysis also brought us some novel clues to further elucidate cancer hallmarks related to pRCC, including autophagy, ErbB signaling pathway, PPAR signaling pathway, and AMPK signaling pathway, which were proved to have close relationship with anchorage-independent growth, 45 cell proliferation, membrane protein driving as well as cell migration 46 of pRCC. The yellow diamonds represent the prognostic SFs.…”
Section: Discussionmentioning
confidence: 99%